English Homonym and Polysemy Words Through Semantic Approach: Novels Woy & The Dancer - Ayu Bandu Retnomurti (Deiksis, 2021)
Every single word or sentence we utter every day should carry particular meaning that our listener can digest well. When we speak or write something with words contained in it, the meaning is considered as being contributed to it. This research aims to study some words which are identified similar by pronunciation and spelling, but the meaning may be either different or similar. This research was undertaken by the researcher used type of descriptive qualitative method seen from the objective of research and qualitative research seen from the inquiry mode used. The results of the research are the researcher found that there are ten homonym words and five polysemy words found in novels Waiting on You and the Dancer.